2012
DOI: 10.2215/cjn.10071011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Patient Education Program on Disparities in Kidney Transplant Evaluation

Abstract: SummaryBackground and objectives In 2007, the Emory Transplant Center (ETC) kidney transplant program implemented a required educational session for ESRD patients referred for renal transplant evaluation to increase patient awareness and decrease loss to follow-up. The purpose of this study was to evaluate the association of the ETC education program on completion of the transplant evaluation process.Design, setting, participants, & measurements Incident, adult ESRD patients referred from 2005 to 2008 were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 21 publications
4
66
0
2
Order By: Relevance
“…Because previous research indicates that behavioral and educational interventions can improve patients' transplant knowledge and attitudinal willingness to pursue DDKT and LDKT (29), an important direction for future research is to test if these interventions also lead to more blacks completing evaluation and receiving LDKTs. Previous studies have indicated that educational interventions in different care settings can increase blacks' knowledge, willingness to pursue, and actual pursuit of DDKT and LDKT (15,29,30). This study also underlines the importance of educationally intervening early and before patients ever present for transplant, particularly in settings like community nephrologists' offices and dialysis centers.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Because previous research indicates that behavioral and educational interventions can improve patients' transplant knowledge and attitudinal willingness to pursue DDKT and LDKT (29), an important direction for future research is to test if these interventions also lead to more blacks completing evaluation and receiving LDKTs. Previous studies have indicated that educational interventions in different care settings can increase blacks' knowledge, willingness to pursue, and actual pursuit of DDKT and LDKT (15,29,30). This study also underlines the importance of educationally intervening early and before patients ever present for transplant, particularly in settings like community nephrologists' offices and dialysis centers.…”
Section: Discussionsupporting
confidence: 50%
“…Although a patient's health insurance is not modifiable by health care providers in transplant or dialysis centers, we recognize that policylevel interventions could influence the impact of these variables. Evidence presented in this paper and by others (11,13,15) that insurance type predicts evaluation completion should be taken under consideration by policymakers. Similarly, there are factors considered less modifiable in this study (for example, depression and anxiety) that actually could be modified for transplant patients with more comprehensive psychological interventions (46,47).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Future research must continue to examine whether these trends persist in a national sample of dialysis centers. However, one promising strategy for improving transplant education in centers with low-SES patients and those in rural areas farther away from transplant centers may be to provide educators with training about transplant's value for their patients; access to more patient-centered educational resources about transplantation; and resources, such as free transportation to a transplant center or more reimbursement for evaluation-related expenses to overcome patients' financial burdens related to transplant (9,27,28). Consistent with prior studies (10,(29)(30)(31), we also found that patients in centers with greater proportions of black patients had significantly lower transplant wait-listing rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few interventions can be undertaken that might show clinical benefit. Specifically, education programs geared towards improving health literacy may improve the outcome in patients identified as at risk status based on low SAI scores [40]. In addition, navigation systems that streamline the process of transplant evaluation could potentially improve access to renal transplantation [41].…”
Section: Novel Ways To Quantity and Estimate Individual Socioeconomicmentioning
confidence: 99%